Gamifying University Writing Centers: An Immersive Learning Experience for Learners with Disabilities - Spathopoulou , Filomachi (American Journal of Education and Learning, 2022)
Starting with the assumption that the inclusion of gamified concepts in the curricula of higher education institutions can bring some novelty to the course materials and encourage active participation, the objective of this article is to examine the extent to which gamification can improve the writing skillset of university students and their motivation, engagement, and performance levels. The article examines gamification through an in-depth and evidence-based discussion that looks into available evidence indicating an abundance of advantages of gamifying higher education courses while at the same time considering the challenges of integrating and implementing gamification into classroom/learning environments. Reference is made to specific games and how they have been used by writing programs in a number of higher education institutions. The discussion includes workable suggestions on how gamification could help University Writing Centers attract students as well as provide better services, especially with regards to students with learning challenges. The article concludes that the best approach to making gamified writing more appealing to students is to follow a framework where the mechanics, dynamics, and emotion elements of the game are tailored to the objectives of the writing course as well as the unique needs and preferences of the learners.